Latent codebook regression for facial feature localisation. Issue 9 (4th April 2016) - Choi, H.C.
Abstract : A new non‐parametric inferring procedure of facial feature localisation which learns regression in latent variable space is introduced. The proposed method uses regression between latent feature and motion spaces spanned by a set of bases of nonlinear feature space and motion vector space which is trained from a large sample set in codebook. Compared with the previous method of using codebook or eigen‐codebook, the proposed method achieved both a significant reduction in the memory consumption without loss of accuracy and a very low computational complexity enough to run in mobile devices.